Case Study on the design optimization of the positive pressure operating room - Oo, Ghaim Man; Kotmool, Komsilp; Mongkolwongrojn, Mongkol (My University, 2024)
Ventilation systems of operating rooms (ORs) are significantly important in preventing postoperative wound infections that can cause morbidity and mortality after surgery in or out of the hospital. This study aims to identify the optimum overpressure for efficient operation while reducing the risk of surgical site infections (SSIs) based on the actual OR with the help of computational fluid dynamics. The species transport model, Lagrangian discrete phase model, and turbulent standard k-ε model are mainly used for the transient numerical study to improve the performance of the OR and reduce SSI cases. Four OR schemes were initially calculated for the best location of the patient on the surgical table. The results revealed that the modified position 90˚ is the best location with the minimum CO2 and BCP concentrations. The investigated operating room could host up to ten surgical members with the optimum overpressure of 5.89 Pa and 0.56 m/s of supply velocity under the standard cleanliness level. Modifying the supply surface area will enhance the performance of the operating room by providing a cleaner zone and maintaining the desired room pressure, even with a low airflow rate. This optimization scheme could guide practical applications in all positively pressurized operating rooms to address issues related to overpressure effects.
Keywords: CO2 and Bacteria-carrying particle (BCP) concentrations; Overpressure; Positive-pressurized clean room; Surgical site infections (SSIs)